Pengaruh Brand Awareness, Brand Image, dan Word-Of-Mouth Terhadap Keputusan Pembelian Konsumen Traveloka Di Kota Malang (Studi Kasus pada pengguna Traveloka Kota Malang) - Satrio, Al Fatkhan Fajar; Maslichah, Maslichah; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Brand Awareness, Brand Image, and Word-Of-Mouth on Consumer Purchase Decisions of Traveloka in Malang City. This is a correlational study with a quantitative approach. The population of this research is the residents in Malang City who are users of Traveloka. The sampling technique used is purposive sampling with a sample of 75 respondents. The data for this research were obtained through questionnaire distribution. The data analysis for this research uses multiple linear regression analysis. This study contributes to understanding the factors influencing consumer purchase decisions of Traveloka in Malang City. The results of this research indicate that Brand Awareness, Brand Image, and Word-Of-Mouth have an influence on Consumer Purchase Decisions of Traveloka in Malang City. Simultaneously, Brand Awareness, Brand Image, and Word-Of-Mouth have an influence on the Consumer Purchase Decisions of Traveloka in Malang City. Keywords: Purchase Decisions, Brand Awareness, Brand Image, Word-Of-Mouth